Management of Moving Class Learning System Through Deep Learning Approach to Improve Students' Learning Interest in Aiza Hafizh Integrated Islamic Kindergarten - Teti Ratnawulan; Badri Zaman; Abuy Abuy; Ira Setiani; Enyi Masrukoyah; Imam Asrofi (Edumaspul: Jurnal Pendidikan, 2025)
Learning is an interaction process between educators and students in teaching and learning activities, supported by learning resources in a learning environment to achieve specific goals. Engaging learning is supported, among other things, by the teacher's creativity in conditioning the class, which can influence students' learning interest. This study aims to analyze the application of moving class learning system management through a deep learning approach to increase students' interest in learning at IT Aiza Hafizh Kindergarten, Cianjur Regency. The research method used is a case study with a qualitative descriptive approach, with data collection techniques through observation, interviews, and documentation studies. The results of the research that has been conducted indicate that the implementation of the Moving Class Learning System Management through a deep learning approach can increase students' interest in learning at the Aiza Hafizh Integrated Islamic Kindergarten, Cianjur Regency. Students have a desire to learn according to their circumstances, abilities, needs, and characteristics, one of which is supported by moving class learning that can increase their interest in learning. The main obstacle faced is that teachers understand deep learning comprehensively and the limited supporting facilities for moving classes. The proposed solutions include teacher training in managing moving class learning and understanding the concept and practice of deep learning. Implementation of moving class learning through a deep learning approach by utilizing the resources and assets owned by the school. This study recommends the development of teacher competence in learning community activities consistently and sustainably as an effort to create interesting, challenging, and enjoyable learning that is adjusted to the nature and nature of the times of students.